Inflation or Speculative Bubbles? Observing Housing Prices in Türkiye by Using PANICCA and GSADF Methods - Kevser, Mustafa; Altaylar, Merve; Bingöl, Ufuk; Yaşar, Zaim Reha (Ekonomika, 2025)
This paper delves into the fundamental reasons behind the non-stationary behavior of Housing Prices (HP) in different regions of Türkiye, which have witnessed an intensified surge fueled by recent aggressive fluctuations. The primary objective is to ascertain whether the driving force behind the escalating HP stems from a housing bubble, or if it can be predominantly attributed to the unprecedented levels of inflation that Türkiye has been experiencing in recent times. This study adopted a comprehensive approach by employing advanced panel PANICCA and GSADF cointegration test techniques to identify the presence of common factors between HPI and inflation from January 2010 to January 2023 to resolve this dilemma. The outcomes strongly suggest that the observed stationarity in HPI predominantly originates from the influence of common factors. More importantly, it has been revealed that disregard of the relevant common variables in the standard factor model may lead to misleading conclusions, such as the misidentification of housing bubbles. This underscores the significance of accurately accounting for the impact of common factors in order to avoid potential distortions in assessing market dynamics and potential risks.
Keywords: Price bubbles; house prices; inflation; panel GSADF; PANICCA